Nascent Quality Issues in the Context of Process-based Paradigm Shift in the Elementary Classes of Kerala - kumar, N. Suresh (JOURNAL OF INDIAN EDUCATION, 2010)
Education, in its broadest sense, refers to the ways in which people learn skills and gain knowledge and understanding about the world, and about themselves. Kerala was declared a ‘Fully Literate State’ in 1991 and is the only state in India where over 90 per cent of the people can read and write. This happens due to the free and compulsory education provided to all children up to the age of 14 years. Apart from this, the government is taking every possible step to improve the quality and standard of education. The new education system implemented in Kerala in which the students and parents decides the quality of the teacher. The article examines that though it has highest literacy rate there are some loopholes in the education system, like lack of competentcy in class–teacher relations. The article also explores the unhealthy practices which are growing in unaided private schools against Children’s rights. Eventhough Kerala has achieved universal elementary education there are rooms for improvement in the quality of teaching-learning process.